2023
DOI: 10.1177/00380261231159524
|View full text |Cite
|
Sign up to set email alerts
|

Breaking climate justice ‘silence’ in everyday life: The environmentalist killjoy, negotiation and relationship risk

Abstract: The moral and justice dimensions of climate change are uncomfortable and commonly avoided in the conversations of day-to-day UK life. This ‘silence’ impedes the genesis of a public discourse to drive justice-oriented social and political change. Two social realms identified as silence-breaking are social movements and personal relationships, yet the potential of this intersection has yet to be explored. This article applies Goffman’s theories of interaction to a qualitative study of UK-based climate activists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…There is also limited information about those who do not engage in interpersonal communication about climate change and the perceived barriers to engaging in these conversations. However, Howard [ 12 ] found that some environmentalists do not engage in climate change conversations due to fears of harming relationships. Understanding the content of climate change conversations and barriers to engaging in these conversations may be useful in developing messages and methods to facilitate peer communication about climate change that can lead to meaningful collective climate actions.…”
Section: Introductionmentioning
confidence: 99%
“…There is also limited information about those who do not engage in interpersonal communication about climate change and the perceived barriers to engaging in these conversations. However, Howard [ 12 ] found that some environmentalists do not engage in climate change conversations due to fears of harming relationships. Understanding the content of climate change conversations and barriers to engaging in these conversations may be useful in developing messages and methods to facilitate peer communication about climate change that can lead to meaningful collective climate actions.…”
Section: Introductionmentioning
confidence: 99%